The Involvement of Interleukin (IL)-15 in Regulating the Differentiation of Granulated Metrial Gland Cells in Mouse Pregnant Uterus - Ye, Weiguo (The Rockefeller University Press, 1996)
Previous studies have suggested that granulated metrial gland (GMG) cells are bone marrow– derived lymphoid cells, which differentiate in situ in the mouse pregnant uterus into natural killer (NK)–like cells. Similar to NK cells, GMG cells express an abundant level of cytolytic mediators such as perforin. The factor(s) regulating the differentiation of GMG cells remain(s) to be identified, although cytokines previously implicated in the stimulation/activation of NK cells (e.g., IL-2, IL-6, IL-7, and IL-12) can be considered as potential candidates. Recently, IL-15, a novel cytokine, which displays biological activities similar to IL-2, has also been shown to be capable of activating NK cells. Using reverse transcription–polymerase chain reaction (RT-PCR) analysis, we have demonstrated in the present study that IL-15 and its cognate receptor, but not the other cytokines, are expressed in the mouse pregnant uterus, with a time course concomitant with those of cytolytic mediators in differentiated GMG cells. Moreover, IL-15, though not IL-2, is capable of inducing the expression of perforin and granzymes in pregnant uterine tissues explanted in vitro. Data obtained from in situ hybridization study have suggested that the macrophages present in the pregnant uterus may be responsible for the production of IL-15. These results suggest that IL-15 is involved in regulating the differentiation of GMG cells during mouse pregnancy.